1996
DOI: 10.1029/96gl03020
|View full text |Cite
|
Sign up to set email alerts
|

Crustal thickness variations beneath the peninsular ranges, southern California

Abstract: We investigate the crustal thickness under the Peninsular Ranges using P‐to‐S converted phases of teleseismic body waves recorded on a temporary broadband seismometer array and isolated by the receiver function method. Ps minus P times at sites west of a compositional boundary that separates the Peninsular Ranges batholith into east and west zones indicate a relatively flat, deep Moho. Ps minus P times at sites east of the compositional boundary decrease eastward, Moho depth estimates (made from the Ps delays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 13 publications
7
37
0
Order By: Relevance
“…More recently, taking advantage of the large number of broadband seismic stations and the related wealth of high-quality data, regional tomographic V p and V p /V s models have been constructed (e.g., Hauksson and Haase, 1997;Hauksson, 2000) based upon P and S-P travel times from local earthquakes and controlled artificial sources. The 3D shape of the southern California Moho has also been imaged (e.g., Ichinose et al, 1996;Lewis et al, 2000;Zhu and Kanamori, 2000). Based upon the teleseismic receiver function technique, Zhu and Kanamori (2000) have shown that very significant variations of Moho depth exist in the region, from 21 to 37 km, with a regional average of 29 km.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, taking advantage of the large number of broadband seismic stations and the related wealth of high-quality data, regional tomographic V p and V p /V s models have been constructed (e.g., Hauksson and Haase, 1997;Hauksson, 2000) based upon P and S-P travel times from local earthquakes and controlled artificial sources. The 3D shape of the southern California Moho has also been imaged (e.g., Ichinose et al, 1996;Lewis et al, 2000;Zhu and Kanamori, 2000). Based upon the teleseismic receiver function technique, Zhu and Kanamori (2000) have shown that very significant variations of Moho depth exist in the region, from 21 to 37 km, with a regional average of 29 km.…”
Section: Introductionmentioning
confidence: 99%
“…These studies include both Bouguer gravity data (Oliver, 1980;Fuis et al, 1982;Weslow, 1985;Jachens, 1986) and three-dimensional imaging of P wave velocities from earthquakes (Magistrale and Sanders, 1995), and indicate a large density contrast (Ͼ0.035 g cm ‫1מ‬ ) between western and eastern zones of the batholith to a depth of at least 22 km, and probably through the entire crust. Other studies have also noted considerable contrast in Moho depths across the compositional boundary using teleseismic receiver function techniques (Ichinose et al, 1996;Lewis et al, 2000;Richards-Dinger and Shearer, 1997) and reflection seismic studies (Zhu and Kanamori, 2000). Ichinose et al (1996) and Lewis et al (2000) determined a relatively deep and flat Moho (37-41 km depth) beneath the western PRb that changed across the transition zone to an eastward-shallowing Moho that decreases to ϳ25 km depth beneath the eastern PRb.…”
Section: °114°112°3mentioning
confidence: 95%
“…Other studies have also noted considerable contrast in Moho depths across the compositional boundary using teleseismic receiver function techniques (Ichinose et al, 1996;Lewis et al, 2000;Richards-Dinger and Shearer, 1997) and reflection seismic studies (Zhu and Kanamori, 2000). Ichinose et al (1996) and Lewis et al (2000) determined a relatively deep and flat Moho (37-41 km depth) beneath the western PRb that changed across the transition zone to an eastward-shallowing Moho that decreases to ϳ25 km depth beneath the eastern PRb. They attributed this shallowing Moho to crustal thinning resulting from Neogene extension in the Salton Trough-Gulf of California extensional province.…”
Section: °114°112°3mentioning
confidence: 95%
“…Due to differences in the thicknesses of the second and third layers, the depth to the Moho is 42 km for the NB model and 35 km for the SC model. At latitudes between ~32.8° and 33.5° N (southern California), Ichinose et al (1996) and Lewis et al (2000) put the Moho at a depth of ~35 km. At latitude ~31° N (north of Baja California, at Sierra San Pedro Mártir), Lewis et al (2001) found that the depth to the Moho is 43 km.…”
Section: Crustal Model and Initial Source Parametersmentioning
confidence: 99%